The Effect of Artificial Intelligence (AI)-Based Learning Models on Students' Motivation and Learning Interests (Case Study at SMA Negeri 2 Tabang Kutai Kartanegara) - Yohanes Dedi Kurniawan; Sucipto Sucipto; Victor Maruli Tua L. Tobing (FKIP - Universitas Riau, 2026)
The research is motivated by the transformative potential of Artificial Intelligence (AI) in education and the challenges of implementation in disadvantaged areas, which create a gap in students' motivation and interest in learning. The purpose of the study was to analyze the influence of AI-based learning models on increasing students' motivation and learning interest at SMA Negeri 2 Tabang, Kutai Kartanegara. The study used a qualitative approach of a case study with thirty student subjects. Data were collected through observation (10 indicators of interest and ten indicators of motivation), interviews, and documentation. Research shows that AI-based models significantly and simultaneously improve both aspects, which is evident from 9 out of ten indicators of interest and all ten indicators of motivation seen. This improvement is fueled by the personalization of exploration and instant feedback from AI, which creates a collaborative and student-centered learning environment. Research proves that despite infrastructure constraints, managed AI integration can transform the dynamics of learning in disadvantaged areas. It is recommended that schools develop guidelines for the use of AI and conduct prompt drafting training for teachers.